2023
DOI: 10.3390/plants12233946
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Novel Reference Genes in Different Rice Plant Tissues through Mining RNA-Seq Datasets

Xin Liu,
Yingbo Gao,
Xinyi Zhao
et al.

Abstract: Reverse transcription quantitative real-time PCR (RT-qPCR) is arguably the most prevalent and accurate quantitative gene expression analysis. However, selection of reliable reference genes for RT-qPCR in rice (Oryza sativa) is still limited, especially for a specific tissue type or growth condition. In this study, we took the advantage of our RNA-seq datasets encompassing data from five rice varieties with diverse treatment conditions, identified 12 novel candidate reference genes, and conducted rigorous evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…The two most stable reference genes in leaves, stems, and roots were CYP and TUA, PGK and PPP2R3, and TUA and EF-1α, respectively. Similar results of varied expressions in different tissues have been reported in some plant species [4,9,28]. From the above results, we also found that the expression levels of reference genes were not always stable across different tissues in A. venetum.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The two most stable reference genes in leaves, stems, and roots were CYP and TUA, PGK and PPP2R3, and TUA and EF-1α, respectively. Similar results of varied expressions in different tissues have been reported in some plant species [4,9,28]. From the above results, we also found that the expression levels of reference genes were not always stable across different tissues in A. venetum.…”
Section: Discussionsupporting
confidence: 89%
“…Quantification of specific mRNA is a fundamental requirement for analyzing gene expression. At present, Northern blotting, microarray analysis, quantitative real-time PCR (qRT-PCR), and RNA sequencing are employed to quantify specific mRNA levels in diverse tissues of an organism [2][3][4]. Among them, qRT-PCR emerges as a highly dependable technique for analyzing gene expression, primarily owing to its sensitivity, reproducibility, specificity, and capacity for high yield [5,6].…”
Section: Introductionmentioning
confidence: 99%